A novel printed radiating microwave structure - Chong, Joshua Wei Kuang. (2011)
A microstrip-line fed novel microwave waveguide was optimized for efficient excitation (or feed) arrangement and low loss. The waveguide was then modified as an antenna by introducing a slot. For each waveguide structure and antenna structure in the design process, simulation of S-parameters and radiation characteristics was carried out using CST Microwave Studio. After that, the final design was fabricated, and simulation results were verified by measurements. S-parameters were measured with a network analyzer; radiation characteristics were measured in a microwave anechoic chamber. Preliminary results showed that there was some agreement between measurement and simulation.